Reconstructing the Concept of Uang Panai in South Sulawesi: A Maqāṣid al-Sharī‘ah Approach for Revitalizing Women-Friendly Islamic Values - Rasyid, Yanuriansyah Ar; Aziz, Fahruddin; Djamaludin , Djamaludin; Tyas, Putri Rohmaning (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Uang panai is a significant issue that often hinders individuals from getting married due to the high financial demands imposed by the bride's family. These demands can sometimes thwart marriage aspirations. This study explores the reconstruction and revitalization of uang panai using Muhammad Syahrur's limit theory to make it more affordable and achievable for men. The research adopts a descriptive-analytical approach, a method that intricately describes specific phenomena or events and subsequently analyzes data to understand the emerging relationships and patterns. The findings indicate that by applying the minimum (al-hadd al-adna) and maximum (al-hadd al-a'la) limits, uang panai can be regulated based on the individual's income while maintaining the honor and dignity of the woman.